PENGGUNAAN MEDIA PERMAINAN MONOPOLI MELALUI PEMBELAJARAN KOOPERATIF PADA MAHASISWA FISIKA FAKULTAS TARBIYAHDENGAN KONSEP TATA SURYA - Fitriyawany Fitriyawany (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
The conducted study concerns about the use of Monopoly game as media in Cooperative Learning on the concept of the Solar System for Students of Physics in Tarbiyah faculty aiming to see the students' mastery of learning outcomes and performance. The study was a Quasi Experimental Research. The population used in the study was all students majoring in Physic Education with a sample of the7th semester students of 2010/2011 academic year. The method of data collection used is testing and observation. Data were analyzed by using the statistical percentage. The result shows there were 90.32% of students passed individually, which therefore the students' learning results were completed classically. In addition, the students' performance on cognitive, affective, and psychomotor in the experimental class also showed positive results. Therefore, it can be concluded that the use of monopoly game as media in cooperative learning on the concept of the Solar System have a positive impact to the quality of learning process.